The Association of Body Image Perception With Dietary and Physical Activity Behaviors Among Adolescents in Indonesia. Issue 1 (June 2021) - Niswah, Ilyatun; Rah, Jee Hyun; Roshita, Airin
Background: Growing evidence highlights the linkage between body image, eating, and exercise behaviors among adolescents. Objective: This study aims to determine the association between body image perception, nutritional status, and dietary and physical activity behaviors among adolescents in Indonesia. Methods: A cross-sectional household survey was conducted among a representative sample (n = 2160) of adolescent girls and boys aged 12 to 18 years in Klaten and Lombok Barat districts. The association between adolescents' body image, their diets, and physical activity patterns was determined using complex samples Cox's regression analysis. Separate multivariate models were developed for adolescent girls and boys. Results: Physical appearance was considered important to nearly all adolescents. Approximately 11% of girls and 14% of boys were overweight or obese, the majority of whom (∼70%) correctly perceived themselves as overweight or obese. More of overweight or obese adolescents felt unhappy about their perceived weight than their thin counterparts. With respect to the overweight/obese girls, the adolescents' perceptions of being overweight or obese was associated with a 63% reduction in the prevalence of overweight/obese girls consuming fatty snacks, such as deep-fried crackers (adjusted prevalence ratio (PR): 0.37, 95% confidence interval (CI): 0.19-0.71) and a 40% reduction in the prevalence of overweight/obese girls engaging in moderate-intensity physical activity (adjusted PR: 0.60, 95% CI: 0.38-0.94), after adjusting for potential confounders. No association between body image and eating and physical activity behaviors was observed among adolescent boys. Conclusions: Body image may be one of the most important determinants of dietary and physical activity behaviors, and thus future efforts to foster healthy eating and physical activity behaviors among Indonesian adolescents need to address body image concerns.